Clinical effects of laparoscopic surgery for the treatment of endometriosis and endometriosis-fertility: A retrospective study of 226 cases - Li, Haiyan; Han, Yingxue; Cai, Yuru; Su, Xiaojuan; Tan, Lixia (Frontiers in Surgery, 2023)
Introduction: To investigate the clinical effects of laparoscopic surgery(LS) for the treatment of endometriosis(ES) and endometriosis-fertility. Methods: Two hundred and twenty-six patients with endometriosis who underwent laparoscopic surgery (LS group, n=176) or laparotomy (LT group, n=50) at Third Hospital of Shijiazhuang City from June 2011 to June 2013 were included in this study, and their clinical outcomes for endometriosis and infertility were compared. All patients were followed up for one year after surgery to investigate postoperative pregnancy in endometriosis. Results: The operative time between LS group and LT group was not statistically significant (P>0.05); however, the length of stay in hospital and blood loss in the LS group were significantly different from those in LT group (P<0.05). The incidence rates of postoperative symptoms were lower in the LS group than in the LT group (P<0.05). The postoperative pregnancy rates in the two groups were significantly different including the infertility patients (P<0.05) . Conclusions: Compared with LT, LS significantly reduces pain and improves quality of life in women with endometriosis. These results can provide a reference for the clinical treatment of endometriosis.